سيكولوجية الصورة الشعرية في الشعر الصوفي ياسين بن عبيد نموذجا - عتبي، عبد الرحمان, حواس، محمد شمس الدين (جامعة الشهيد حمه لخضر بالوادي, 2018)
تهدف هذه الدراسة إلى محاولة الكشف عن المعنى والدلالة العميقة التي يختص بها النص المعاصر، وما يستفز المتلقي من جماليات في التصوير، والبعد النفسي للشاعر في الخصائص الإبداعية والجمالية. من خلال سيكولوجية الصورة في الشعر الصوفي ياسين بن عبيد نموذجاً للكشف عن تجليات السيكولوجية للصورة في ثلاث زوايا اليقظة الحسية واليقظة الباطنية والصورة المشخصة.The purpose of this study is to attempt to uncover the profound meaning and signicance of contemporary text. And what provokes the recipient of esthetics in photography . and the psychological dimension of the poet in the creative and esthetic characteristics through the psychology of the image in mystical poetry yacin ben ibid a model for detecting the psychological manifestations of the image in the three corners of sensory alertness inner alertness and image.
Keywords: السيكولوجية -الصورة - الشعرية- الصوفية; . Psychology - picture - noodles - woolen